The gender wealth gap near retirement in Canada - Tessa LoRiggio; Todd Morris (Institute of Labor Economics (IZA), 2024)
The gender pay gap not only affects women's financial security during their working lives but also their wealth available for retirement. This note reveals a large gender wealth gap in Canada among singles near retirement. Using a repeated national wealth survey from 1999 to 2019, we find an average wealth gap favouring men at ages 45-59 of 56,000 or 16%, and the estimated gap rises to 96,000 or 27% after accounting for gender differences in demographic characteristics. There is no evidence that the wealth gap is narrowing, which is largely explained by the gender earnings gap. Previously married women are particularly disadvantaged, which may reflect the persistent earnings penalties faced by women who have children.
Keywords: D31; J31; 330; gender wealth gap; gender earnings gap; retirement wealth; business equity; costs of divorce